Ways of Greening Using Plants and Gardens for Healthy Work and Living Surroundings - Famulari, Stevie (Productivity Press, 2023)
Ways of Greening focuses on rethinking working and living spaces and understanding how "greening" can make them healthier and their occupants happier. This book teaches how to see unique ideas for spaces, and some of the materials needed to create the designs